2001
DOI: 10.1590/s1517-83822001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties of clove oil (Eugenia caryophylata) in sugar solution

Abstract: The effect of temperature, concentration and contact time on the fungicidal effect of clove oleoresin dispersed in a concentrated sugar solution at 21 and 37ºC, and clove oleoresin at 0.2 to 0.8% (v/v) was studied. The test microorganisms were Candida albicans, Penicillium citrinum, Aspergillus niger and Trichophyton mentagrophytes. The fungicidal effect was enhanced at 37ºC; at this temperature short contact times (e.g. 1 min.) were enough to eliminate a microbial inoculum of 10 6 c.f.u./ml of C. albicans. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Clove oil was dominated by eugenol and there are reports stating that eugenol and clove oil are antifungal agents (Nú ñ ez et al 2001;Chami et al 2004). But in this study, the inhibitory effect of clove oil on FOC is low compared to A. porri.…”
Section: Discussionmentioning
confidence: 99%
“…Clove oil was dominated by eugenol and there are reports stating that eugenol and clove oil are antifungal agents (Nú ñ ez et al 2001;Chami et al 2004). But in this study, the inhibitory effect of clove oil on FOC is low compared to A. porri.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol and eugenol are the main components of clove responsible for its fungicidal characteristics against onychomycosis isolated fungi, T. mentagrophytes and Candida albicans [31,67,68]. Interestingly, Núñez et al [69] reported the fungicidal activity of the mixture of a concentrated sugar solution with clove oleoresin by decreasing the inoculum size of fungi. Chami et al [70] revealed remarkable morphological deterioration with cellular deformation in Saccharomyces cerevisiae cells caused by clove oil.…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
“…The main antifungal action appears to be exerted on the cellular membrane (Cox et al, 2001). Eugenol has shown antifungal activity against Candida albicans and Trichophyton mentagrophytes (Tampieri et al, 2005) and Núñez et al (2001) demonstrated that the mixture of clove oleoresin with concentrated sugar solution produced a strong fungicidal effect by reducing fungi inoculum size. In a recent report, SEM micrographs showed significant morphological damage with cellular deformity to Saccharomyces cerevisiae cells by clove oil (Chami et al, 2005).…”
Section: Fungicidal Activitymentioning
confidence: 99%